Periodic Unobserved Cycles in Seasonal Time Series with an Application to US Unemployment - Siem Jan Koopman; Marius Ooms; Irma Hindrayanto (Tinbergen Institute, 2006)
This paper discusses identification, specification, estimation and forecasting for a general class of periodic unobserved components time series models with stochastic trend, seasonal and cycle components. Convenient state space formulations are introduced for exact maximum likelihood estimation, component estimation and forecasting. Identification issues are considered and a novel periodic version of the stochastic cycle component is presented. In the empirical illustration, the model is applied to postwar monthly US unemployment series and we discover a significantly periodic cycle. Furthermore, a comparison is made between the performance of the periodic unobserved components time series model and a periodic seasonal autoregressive integrated moving average model. Moreover, we introduce a new method to estimate the latter model.
Keywords: C22; C51; E32; E37; 330; Unobserved component models; state space methods; seasonal adjustment; time–varying parameters; forecasting